Agri-food firms’ attitude toward digital data exploitation in the product development - Frau, Moreno; Keszey, Tamara (Marketing & Menedzsment, 2023)
THE AIMS OF THE PAPER This paper explores digital data exploitation behaviours and shows how these conducts change according to the data sources used by agri-food firms when developing their products. METHODOLOGY We adopt an exploratory multiple-case study to provide a theoretical framework for agri-food firms utilising digital data for product development. MOST IMPORTANT RESULTS The article shows two prominent firms’ behaviours that we labelled data explorers and data receivers and a third behaviour which is a combination of the main ones. RECOMMENDATIONS This article offers guidelines to support agri-food firms to distinguish how such firms may benefit from the digital transformation by gaining competitiveness improving production efficiency and supporting the development of their products. Acknowledgments: This paper has received funding from the European Union’s Horizon 2020 research and innovation programme under the Marie Sklodowska-Curie grant agreement No 101030185. This article is an outcome of the project FooDization.